Factors associated with HIV infection among female sex workers in Brazil. (May 2018) - Szwarcwald, Célia Landmann; Damacena, Giseli Nogueira; de Souza-Júnior, Paulo Roberto Borges; Guimarães, Mark Drew Crosland; de Almeida, Wanessa da Silva; de Souza Ferreira, Arthur Pate; Ferreira-Júnior, Orlando da Costa; Dourado, Inês
Abstract: Background: Female sex workers (FSWs) are one of the most-at-risk population groups for human immunodeficiency virus (HIV) infection. This paper aims at identifying the main predictors of HIV infection among FSW recruited in the 2nd Biological and Behavioral Surveillance Survey in 12 Brazilian cities in 2016. Method: Data were collected on 4245 FSW recruited by respondent driven sampling (RDS). Weights were inversely proportional to participants' network sizes. To establish the correlates of HIV infection, we used logistic regression models taking into account the dependence of observations resultant from the recruitment chains. The analysis included socio-demographic sex work characteristics, sexual behavior, history of violence, alcohol and drug use, utilization of health services, and occurrence of other sexually transmitted infections (STIs). Results: HIV prevalence was estimated as 5.3% (4.4%–6.2%). The odds ratio (OR) of an HIV-positive recruiter choosing an HIV-positive participant was 3.9 times higher than that of an HIV-negative recruiter ( P  < .001). Regarding socio-demographic and sex work characteristics, low educational level, street as the main work venue, low price per sexual encounter, and longer exposure time as a sex worker were found to be associated with HIV infection, even after controlling for the homophily effect. The OR of being HIV infected among FSW who had been exposed to sexual violence at least once in a lifetime (OR = 1.5, P  = .028) and the use of illicit drugs at least once a week were highly significant as well, particularly for frequent crack use (OR = 3.6, P  < .001). Among the sexual behavior indicators, not using condoms in some circumstances were significantly associated with HIV infection (OR = 1.8, P  = .016). Regarding the occurrence of other STI, the odds of being HIV infected was significantly higher among FSW with a reactive treponemal test for syphilis (OR = 4.6, P  < .001). Conclusions: The main factors associated with HIV infection identified in our study characterize a specific type of street-based sex work in Brazil and provided valuable information for developing interventions. However, there is a further need of addressing social and contextual factors, including illicit drug use, violence, exploitation, as well as stigma and discrimination, which can influence sexual behavior.